Founder event and its effect on genetic variation in translocated populations of noble crayfish (Astacus astacus) - Bláha, Martin; Žurovcová, Martina; Kouba, Antonín; Policar, Tomáš; Kozák, Pavel (Journal of applied genetics, 2016)
Establishing translocated populations is a common process to preserve and maintain genetic diversity of threatened species. In 2001, three translocated populations of noble crayfish (Astacus astacus) were established in the Czech Republic, founded by either adult or juvenile individuals from three particular source populations. We assessed genetic diversity at seven microsatellite loci after one decade (assumed three generations) from establishment. Although the translocated populations exhibited a slight but non-significant reduction in genetic diversity (A R = 2.2-5.0; H O = 0.11-0.31), the most striking result was generally very low genetic diversity in source populations (A R = 3.0-5.3; H O = 0.15-0.38). Similarly, a high degree of inbreeding (F IS = 0.36-0.60) demonstrates the nature of source populations, already affected by isolation and small size. In spite of that, based on the results of this study, the establishment of new translocated noble crayfish populations was successful, since there is no significant decline in genetic variability and all populations are still viable. Although source populations did not exhibit high genetic diversity, their distinctiveness makes them possible to use for conservation purposes. Continued monitoring is necessary to track the long-term progress of the translocation program, including other parameters describing the state of the population, such as the occurrence and frequency of diseases or morphological changes.
Keywords: Founder Effect; Population Density; zachování přírodních zdrojů; Animals; Female; Conservation of Natural Resources; ženské pohlaví; Bottleneck; inbreeding; hustota populace; Microsatellites; Astacoidea; Genetic Variation; Genetics, Population; Conservation; Male; efekt zakladatele; severní raci; Czech Republic; Microsatellite Repeats; alely; Sequence Analysis, DNA; Inbreeding; Česká republika; Alleles; Homozygote excess; zvířata; mužské pohlaví; sekvenční analýza DNA; genetická variace; mikrosatelitní repetice; populační genetika